Literasi dan Media Pembelajaran Interaktif pada Guru SD - Mulyawati, Ima; Pujiyanti, Depi (STKIP Andi Matappa, 2021)
Teachers experienced difficulties in learning carried out during the Covid 19 pandemic, especially literacy in learning and Â innovative learning media. The power points made by the teachers have not led to interactive learning media. The teachers have not mastered and used learning media with Fastone Capture, Bandicam, Powtoon, Kinmaster, and Xrecorder in learning. Based on these problems, this service activity offers comprehensive training consisting of a preparatory stage in the form of surveys and interviews regarding partners' conditions, the implementation stage in the form of (1) exposure to learning literacy, (2) exposure to interactive learning media material, (3) interactive learning media assistance. The last stage is evaluation by providing a questionnaire about service activities and follow-up on further service activities. Community service activities are carried out by webinars. This service activity went well, as seen with 100% of the teachers attending this service, 90% of the participants stated that they were satisfied with this activity.